Spinal Central Effects of Peripherally Applied Botulinum Neurotoxin A in Comparison between Its Subtypes A1 and A2 - Koizumi, Hidetaka; Goto, Satoshi; Okita, Shinya; Morigaki, Ryoma; Akaike, Norio; Torii, Yasushi; Harakawa, Tetsuhiro; Ginnaga, Akihiro; Kaji, Ryuji (Frontiers in Neurology, 2014)
Because of its unique ability to exert long-lasting synaptic transmission blockade, botulinum neurotoxin A (BoNT/A) is used to treat a wide variety of disorders involving peripheral nerve terminal hyperexcitability. However, it has been a matter of debate whether this toxin has central or peripheral sites of action. We employed a rat model in which BoNT/A1 or BoNT/A2 was unilaterally injected into the gastrocnemius muscle. On time-course measurements of compound muscle action potential (CMAP) amplitudes after injection of BoNT/A1 or BoNT/A2 at doses ranging from 1.7 U to 13.6 U, CMAP amplitude for the ipsilateral hind leg was markedly decreased on the 1st day, and this muscle flaccidity persisted up to the 14th day. Of note, both BoNT/A1 and BoNT/A2 administrations also resulted in decreased CMAP amplitudes for the contralateral leg in a dose-dependent manner ranging from 1.7 to 13.6 U, and this muscle flaccidity increased until the 4th day and then slowly recovered. Immunohistochemical results revealed that BoNT/A-cleaved SNAP-25 (synaptosomal-associated protein of 25 kDa) appeared in the bilateral ventral and dorsal horns 4 days after injection of BoNT/A1 (10 U) or BoNT/A2 (10 U), although there seemed to be a wider spread of BoNT/A-cleaved SNAP-25 associated with BoNT/A1 than BoNT/A2 in the contralateral spinal cord. This suggests that the catalytically active BoNT/A1 and BoNT/A2 were axonally transported via peripheral motor and sensory nerves to the spinal cord, where they spread through a transcytosis (cell-to-cell trafficking) mechanism. Our results provide evidence for the central effects of intramuscularly administered BoNT/A1 and BoNT/A2 in the spinal cord, and a new insight into the clinical effects of peripheral BoNT/A applications.